A Novel Trans-Tracheostomal Retrograde Inhalation Technique Increases Subglottic Drug Deposition Compared to Traditional Trans-Oral Inhalation - Raviv Allon; Saurabh Bhardwaj; Josué Sznitman; Hagit Shoffel-Havakuk; Sapir Pinhas; Elchanan Zloczower; Yael Shapira-Galitz; Yonatan Lahav (MDPI AG, 2023)
Subglottic stenosis represents a challenging clinical condition in otolaryngology. Although patients often experience improvement following endoscopic surgery, recurrence rates remain high. Pursuing measures to maintain surgical results and prevent recurrence is thus necessary. Steroids therapy is considered effective in preventing restenosis. Currently, however, the ability of trans-oral steroid inhalation to reach and affect the stenotic subglottic area in a tracheotomized patient is largely negligible. In the present study, we describe a novel trans-tracheostomal retrograde inhalation technique to increase corticosteroid deposition in the subglottic area. We detail our preliminary clinical outcomes in four patients treated with trans-tracheostomal corticosteroid inhalation via a metered dose inhaler (MDI) following surgery. Concurrently, we leverage computational fluid-particle dynamics (CFPD) simulations in an extra-thoracic 3D airway model to gain insight on possible advantages of such a technique over traditional trans-oral inhalation in augmenting aerosol deposition in the stenotic subglottic region. Our numerical simulations show that for an arbitrary inhaled dose (aerosols spanning 1-12 µm), the deposition (mass) fraction in the subglottis is over 30 times higher in the retrograde trans-tracheostomal technique compared to the trans-oral inhalation technique (3.63% vs. 0.11%). Importantly, while a major portion of inhaled aerosols (66.43%) in the trans-oral inhalation maneuver are transported distally past the trachea, the vast majority of aerosols (85.10%) exit through the mouth during trans-tracheostomal inhalation, thereby avoiding undesired deposition in the broader lungs. Overall, the proposed trans-tracheostomal retrograde inhalation technique increases aerosol deposition rates in the subglottis with minor lower-airway deposition compared to the trans-oral inhalation technique. This novel technique could play an important role in preventing restenosis of the subglottis.